Analysis of digital teaching and learning experiences applied during the COVID-19 pandemic on higher education from the best educational practices approach - Moreno Reyes, Hugo; Mondragón Beltrán, Emmanuel Ángel Argenis; Peña Vargas, Carmen Silvia (IE Revista de Investigación Educativa de la REDIECH, 2021)
The COVID-19 pandemic has had a strong impact on the teaching and learning processes, forcing teachers and higher education institutions to move rapidly towards digital education, which brings enormous challenges. In order to find the solutions that have emerged to face the situation and being aware of the need to promote them in the educational community, a descriptive bibliographic review of over 23 practices has been prepared on best educational practices and recommendations published in the last year during the pandemic. For the content’s analysis, the following categories were defined: problems, innovations, practices, effectiveness and the contribution of digital technologies. The results allow us to appreciate that practices were developed around three general aspects: the establishment of a methodological framework for modality transition, the implementation of tutoring mechanisms and the implementation of virtual laboratory models.